Die Würde und der Mut L'Art Moral. - Alvard, Julien; Deroudille, René; Michaux, Henri; de la Motte, Manfred; Nothelfer, Georg; Restany, Pierre; Schauer, Lucie; Tapié, Michel; de Loo, Otto van; Galerie Georg Nothelfer, Berlin-Charlottenburg (Berlin : Henssel Verlag, 1991)
Alechinsky, Pierre ; Appel, Karel ; Armando ; Bacon, Francis ; Baumeister, Willi ; Bissier, Julius ; Bogart, Bram ; Brüning, Peter ; Buchheister, Carl ; Burri, Alberto ; Capogrossi, Giuseppe ; Chaissac, Gaston ; Chillida, Eduardo ; Christo ; Constant ; Corneille ; Cornell, Joseph ; Dahmen, Karl Fred ; Davie, Alan ; Domoto, Hisao ; Dorazio, Piero ; Dubuffet, Jean ; Fautrier, Jean ; Fischer, Lothar ; Francis, Sam ; Gallizio, Pinot ; Giacometti, Alberto ; Gorky, Arshile ; Götz, K.O. (Karl Otto) ; Hartung, Hans ; Heyboer, Anton ; Hoehme, Gerhard ; Imaï, Toshimitsu ; Iseli, Rolf ; Johns, Jasper ; Jorn, Asger ; Kiefer, Anselm ; Kline, Franz ; de Kooning, Willem ; Kounellis, Jannis ; Lakner, Laszlo ; Louis, Morris ; Lucebert ; Macréau, Michel ; Masson, Andre ; Mathieu, Georges ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Menne, Walter ; Messensee, Jürgen ; Michaux, Henri ; Millares, Manolo ; Miotte, Jean ; Moreni, Mattia ; Motherwell, Robert ; Nay, Ernst Wilhelm ; Nitsch, Hermann ; Noël, Georges ; Novelli, Gastone ; Perilli, Achille ; Platschek, Hans ; Pollock, Jackson ; Praschensky, Markus ; Prem, Heimrad ; Rainer, Arnulf ; Rauschenberg, Robert ; Riopelle, Jean-Paul ; Roth, Dieter ; Saura, Antonio ; Schultze, Bernard ; Schumacher, Emil ; Serpan, Jaroslav ; Shiraga, Kazuo ; Sonderborg, K.R.H. ; Soulages, Pierre ; Soutter, Louis ; de Staël, Nicolas ; Stöhrer, Walter ; Sturm, Helmut ; Tàpies, Antoni ; Thieler, Fred ; Tobey, Mark ; Trier, Hann ; Trökes, Heinz ; Twombly, Cy ; Vedova, Emilio ; van Velde, Bram ; Vieira da Silva, Maria Elena ; Voss, Jan ; Winter, Fritz ; Wols ; Zimmer, Hans Peter
biog. p. 286-307
Duits
Engels
Frans
Die Würde und der Mut L'Art Moral, Galerie Georg Nothelfer Berlin-Charlottenburg, 20.04. - 21.09.1991
boek